(NnAU^NAQ ORGANIZACIQ UPRAWLEN^ESKOGO TRUDA (B:s (NNA PRIMERE GOSUDARSTWENNYH U^REVDENIJ (B/s - (NaTAEW(B, (NaRSLAN aBDULKADYROWI^s ((NmOSKWA (B:s (N|KONOMIKA(B,s, 1980)
(NzAKL(B.: (NS(B. 140-142s
Keywords: (NoRGANIZACIQ TRUDAs